(untitled) (CONTINUIDAD Y DISCONTINUIDAD EN EL ESPACIO IBEROAMERICANO, 2026)
In the present work, we propose to evaluate the continuity and discontinuity in translations from Spanish into Macedonian since 1944—the year of the codification of the Macedonian language—to the present day. We are interested in seeing when translations into Macedonian began, how they multiplied over the decades, and whether there were periods of decline or growth in the interest in works by Spanish or Hispano-American authors, while attempting to explain the potential reasons behind these shifts. That is to say, the objective of this study will be to gather and contrast data to interpret the factors that influence the presence or absence of certain authors (prestige, literary prizes, genre, editorial politics) and the general interest in works written in Spanish within the broader landscape of works translated into Macedonian.